FC 005DEPOSITION OF PLATELET-DERIVED MICRO-PARTICLES IN PODOCYTES CONTRIBUTES TO DIABETIC NEPHROPATHY. (29th May 2021) - Huang, Sijia; Lu, Jian; Chen, Pei Pei; Zhang, Jia Xiu; Li, Xue Qi; Liu, Bicheng; Ma, Kun Ling
Abstract: Background and Aims: Diabetic nephropathy (DN) is the leading cause of end-stage renal disease in the developed world. Podocyte injury has been shown to be a critical cellular event in the progression of DN. Our previous studies demonstrated that platelet-derived microparticles (PMPs) mediated endothelial injury in diabetic rats. Therefore, this study aimed to investigate whether the PMPs deposit in podocytes and its potential effects on podocyte injury in DN. Method: Deposition of PMPs in podocytes was checked by immunofluorescent staining and electron microscopy. Renal pathological change and ultra-microstructure were respectively checked by periodic acid-schiff staining and electron microscopy. The protein expression of inflammatory cytokines and extracellular matrix was measured by immunohistochemical staining and Western blot. Results: The PMPs were found to be widely deposited in podocytes of glomeruli in diabetic patients and animal models and closely associated with progression of DN. Interestingly, aspirin treatment significantly inhibited accumulation of PMPs in glomeruli of diabetic rats, accompanied with alleviated mesangial matrix expansion, fusion of foot processes, decreased protein expression of inflammatory cytokines and extracellular matrix secretion. The in vitro study further confirmed the deposition of PMPs in podocytes. Moreover, PMPs stimulation induced phenotype transition of podocytes through decreased protein expression of podocin and increased protein expression of α-SMA and fibronectin, which was correlated with increased production of inflammatory cytokines. Conclusion: Our findings for the first time demonstrated that deposition of PMPs in podocytes contributed to the development of DN.